Psychological Contract Theory Relation to Organizational Citizenship Behavior (OCB) of Flight Attendants - Teguh Setiawan Wibowo (International Journal of Science, Technology & Management, 2022)
In service organizations such as airlines, flight attendants as one of the components that play a direct role in serving the needs of passengers during flights are required to work independently without supervision and have confidence in carrying out job demands since they are accepted as employees. The agreement formed between the flight attendant and the airline is the initial motivation and trust given by the airline to flight attendants as employees known as psychological contracts. A high psychological contract with a reciprocal relationship where the flight attendant's expectations are fulfilled by the airline will make the flight attendant feel valued for her work and empowered. This feeling raises the motivation of flight attendants as employees to be more active by showing OCB. OCB is the behavior of flight attendants as individuals voluntarily outside of their formal job descriptions to support the advancement of the airline where they work. In this article, psychological contracts are an important factor in the growth of OCB in flight attendants, such as arriving to work early, helping coworkers or new employees who are experiencing difficulties, and contributing more to activities organized by airlines.